Energy transfer in aggregated CuInS2/ZnS core-shell quantum dots deposited as solid films. (20th December 2016) - Gardelis, S; Fakis, M; Droseros, N; Georgiadou, D; Travlos, A; Nassiopoulou, A G
Abstract: We report on the morphology and optical properties of CuInS2 /ZnS core-shell quantum dots in solid films by means of AFM, SEM, HRTEM, steady state and time-resolved photoluminescence (PL) spectroscopy. The amount of aggregation of the CuInS2 /ZnS QDs was controlled by changing the preparation conditions of the films. A red-shift of the PL spectrum of CuInS2 /ZnS core-shell quantum dots, deposited as solid films on silicon substrates, is observed upon increasing the amount of aggregation. The presence of larger aggregates was found to lead to a larger PL red-shift. Besides, as the degree of aggregation increased, the PL decay became slower. We attribute the observed PL red-shift to energy transfer from the smaller to the larger dots within the aggregates, with the emission being realized via a long decay recombination mechanism (100–200 ns), the origin of which is discussed.